A comparative analisys of pelvic floor muscle strength in women with stress and urge urinary incontinence - Gameiro, Monica Orsi [UNESP]; Moreira, Eliane Cristina; Ferrari, Renata Spagnoli [UNESP]; Kawano, Paulo Roberto [UNESP]; Padovani, Carlos Roberto [UNESP]; Amaro, João Luiz [UNESP] (Brazilian Soc Urol, 2012)
Aims: To assess pelvic floor muscle (PFM) strength in women with stress urinary incontinence (SUI) and urge urinary incontinence (UUI).Materials and Methods: 51 women were prospectively divided into two groups, according to the symptoms as SUI (G1 = 22) or UUI (G2 = 29). Demographic data, such as number of pads/ 24 hours, number of micturations/ 24 hours and nocturia, delay time of urgent void (i.e., the time period for which an urgent void could be voluntarily postponed), number of parity and vaginal deliveries were obtained using a clinical questionnaire. Objective urine loss was evaluated by 60-min. Pad Test, subjective urine stream interruption test (UST) and visual survey of perineal contraction. Objective evaluations of PFM were performed in all patients (vaginal manometry).Results: Median of age, mean number of pads/ 24 hours, nocturia and warning time were significantly higher in UUI comparing to SUI group. During UST, 45.45% in G1 and 3.44%, in G2, were able to interrupt the urine stream (p < 0.001). The 60-min. Pad Test was significantly higher in G2 compared to G1 women (2.7 +/- 2.4 vs 1.5 +/- 1.9 respectively, p = 0.049). Objective evaluation of PFM strength was significantly higher in the SUI than in the UUI patients. No statistical difference was observed regarding other studied parameters.Conclusion: Pelvic floor muscle weakness was significantly higher in women with UUI when compared to SUI.
Keywords: Pelvic Floor; Women; Urinary Incontinence; Stress; Urinary Incontinence; Urge